Conservation Agriculture With Optimum Fertilizer Nitrogen Rate Reduces GWP for Rice Cultivation in Floodplain Soils - Jahangir, M. M. R.; Bell, R. W.; Uddin, S.; Ferdous, J.; Nasreen, S. S.; Haque, M. E.; Satter, M. A.; Zaman, M.; Ding, W.; Jahiruddin, M.; Müller, C. (Frontiers in Environmental Science, 2022)
Wetland rice cultivation contributes significantly to global warming potential (GWP), an effect which is largely attributed to emissions of methane (CH4). Emerging technologies for wetland rice production such as Conservation agriculture (CA) may mitigate greenhouse gas (GHG) emissions but the effects are not well defined. Investigations were carried out in an irrigated rice field in the fifth crop after conversion of conventional tillage (CT) to strip tillage (ST). Two crop residue levels (low vs high, LR vs HR) and three nitrogen (N) application rates (N1 = 108, N2 = 144 and N3 = 180 kg N ha-1) were laid out in a split-plot experiment with three replicates. Yield-scaled GHG emissions and GWP were estimated to evaluate the impacts of CA on mitigating CH4 and N2O emissions in the rice paddy field. There was 55% higher N2O emission in ST with HR coupled with N3 than that in CT with LR coupled with N1. The N2O emission factors ranged from 0.43% to 0.75% in ST and 0.45% to 0.59% in CT, irrespective of residue level and N rate. By contrast, CH4 emissions were significantly lower in CA than in the conventional practices (CT plus LR). The ST with LR in N2 reduced the GWP by 39% over the GWP in CT with HR in N1 and 16% over the conventional practices. Based on our investigation of the combination of tillage, residue and N rates treatments, the adoption of CA with high and low residue levels reduced the GWP by 10% and 16% due to lower CH4 and N2O emissions than the current management practices. The relatively high N2O emission factors suggest that mitigation of this GHG in wetland rice systems needs greater attention.